Lesotho Public Health Sector Expenditure Review - UNICEF; World Bank (World Bank, Washington, DC, 2018)
This Public Expenditure Review (PER) is the result of collaboration among UNICEF, the World Bank Group, and Lesotho's Ministries of Health and Finance. Senior economists from the Clinton Health Access Initiative provided invaluable support in analyzing health expenditure data. The PER covers a five-year period, from fiscal years (FY) 2011/12 to 2015/16 (in Lesotho, the fiscal year runs from April 1 through March 30). The report describes and analyzes expenditure patterns in Lesotho's public health sector using multiple data sources. Focusing on the Ministry of Health and Social Welfare's (MoH) expenditure, the report identifies opportunities to improve the efficiency, equity, and effectiveness of financial resource use. To present a clear view of health expenditure, the report disaggregates total expenditure in the health system and describes its allocation across cost centers, districts (10 of them in Lesotho), levels of care, and health facilities (hospitals and primary health centers). Specific focus is on allocation of expenditure by economic classifications, and across outsourced health service providers.